Cross-Layer Design for the Physical, MAC, and Link Layer in Wireless Systems. (18th August 2008) - Popovski Popovski, Petar Petar; Ingram Ingram, Mary Ann Mary Ann; Peel Peel, Christian B. Christian B.; Hara Hara, Shinsuke Shinsuke; Toumpis Toumpis, Stavros Stavros
Abstract :